Effect of Roasting Time on The Organoleptic Characteristics of Excelsa Wonosalam Jombang Coffee - Na'im, Muhammad Zainun; Chusnah, Miftachul; Hartanti, Dyah Ayu Sri (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
There are many types of coffee plants in Indonesia, including Robusta, Arabica, Liberika and Excelsa. One type of coffee found in Wonosalam District is excelsa coffee, Wonosalam excelsa coffee is a species of coffee plant in the genus Coffea. The roasting process is the process of developing the aroma and taste of coffee, separated from the inside of the coffee beans by heat treatment. Coffee beans contain organic compounds that give the coffee beans their aroma and taste. This research aims to determine the effect of roasting time on the organoleptic characteristics of Excelsa coffee, and to determine the appropriate length of time for the roasting process of Excelsa coffee. This research uses a qualitative approach, data collection used in this research is in the form of (1) sampling method, (2) interview method, (3) documentation method, (4) questionnaire method. This research used a Completely Randomized Design (CRD), using 3 treatments and 3 repetitions, P1 (10 minutes), P2 (15 minutes), and P3 (20 minutes) using a roasting temperature of 200℃. The data processing method used is the Analysis of Variance (ANOVA) method with a further BNT test at a level of 5%. The results of the research show that the length of roasting time has a significant effect on the color, taste and aroma of Excelsa coffee. The selected results were obtained at a roasting temperature of 200℃ with a roasting time of 15 minutes which had an average color value of 13.53 (dark brown), aroma of 12.42 (fragrant), and taste of 11.30 (like).